Calidad tutorial e hiperactividad en niños de la Institución Educativa Inicial N° 602 Primavera, San Juan Bautista 2023 - Vargas Nolorve, Ingrid Alejandra (2024)
This study determines the relationship between tutoring quality and hyperactivity among students at the Initial Educational Institution N° 602 Primavera San Juan Bautista during the year 2023. Adopting a non-experimental, relational, field, bivariate, and cross-sectional methodological approach, the research encompassed all 77 children enrolled in the institution as its population and sample. A questionnaire and an observation guide, both validated by experts, were used for data collection, along with survey techniques and direct observation. The results revealed a significant negative correlation (Pearson of -0.732) between tutoring quality and hyperactivity, indicating that improvements in tutoring are associated with a reduction in hyperactivity levels. This empirical evidence highlights the importance of implementing effective pedagogical strategies to mitigate hyperactivity among students, as evidenced by the inverse linear trend observed in the dispersion analysis.